The design and mechanics of the multilateral system of access and benefit sharing - Manzella, Daniele (2012)
Seventh chapter of the book Crop Genetic Resources as a Global Commons. Challenges in international law and governance, edited by Michael Halewood, Isabel López Noriega and Selim Louafi and published by Routledge in 2012 as part of the Earthscan book series "Issues in Agricultural Biodiversity"